Espiritualidades e formação humana: rumo à pluralização dos sentidos - Medeiros, Lis Paiva de (Plura, revista de estudos de religião, 2022)
This paper focuses on the search for relation ships, implications and tensions between spirituality and the human formation field. It comes from a masters’ thesis, specifically its moment of bibliographical research in the works by Röhr (2012; 2013); Wilber (2000; 2006; 2020); Boff (1999; 2000); Boff; Betto (2010); Foucault (2004) and Hadot (2008; 2014). The aimistosyn the sise the authors’ proposals on spirituality, fromwhich emerge meanings and implications for human formation and for the field of education. Approximations and distances have been found bet ween the perspectives, although, in general, it is not possible to define a univocalconcept of spirituality that permeates the diversityof the field. We advocate for the onto-epistemological pluralization of the term and field: spiritualities. This proposal indicatesanethical defense of the plurality of experiences of spiritualities, in a secular sense, rooted in everyday life, connecting transcendence and immanence.